Electromagnetic signal penetration in a planetary soil simulant: Estimated attenuation rates using GPR and TDR in volcanic deposits on Mount Etna. Issue 7 (3rd July 2017) - Lauro, S. E.; Mattei, E.; Cosciotti, B.; Di Paolo, F.; Arcone, S. A.; Viccaro, M.; Pettinelli, E.
Abstract: Ground‐penetrating radar (GPR) is a well‐established geophysical terrestrial exploration method and has recently become one of the most promising for planetary subsurface exploration. Several future landing vehicles like EXOMARS, 2020 NASA ROVER, and Chang'e‐4, to mention a few, will host GPR. A GPR survey has been conducted on volcanic deposits on Mount Etna (Italy), considered a good analogue for Martian and Lunar volcanic terrains, to test a novel methodology for subsoil dielectric properties estimation. The stratigraphy of the volcanic deposits was investigated using 500 MHz and 1 GHz antennas in two different configurations: transverse electric and transverse magnetic. Sloping discontinuities have been used to estimate the loss tangents of the upper layer of such deposits by applying the amplitude‐decay and frequency shift methods and approximating the GPR transmitted signal by Gaussian and Ricker wavelets. The loss tangent values, estimated using these two methodologies, were compared and validated with those retrieved from time domain reflectometry measurements acquired along the radar profiles. The results show that the proposed analysis, together with typical GPR methods for the estimation of the real part of permittivity, can be successfully used to characterize the electrical properties of planetary subsurface and to define some constraints on its lithology of the subsurface. Key Points: GPR methodologies for evaluating the loss tangent of volcanic sediments Characterization of electrical properties of a planetary soil simulant Comparison between GPR and TDR measurements